2017
DOI: 10.1523/jneurosci.1076-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

K+Channel Kv3.4 Is Essential for Axon Growth by Limiting the Influx of Ca2+into Growth Cones

Abstract: Membrane excitability in the axonal growth cones of embryonic neurons influences axon growth. Voltage-gated K (Kv) channels are key factors in controlling membrane excitability, but whether they regulate axon growth remains unclear. Here, we report that Kv3.4 is expressed in the axonal growth cones of embryonic spinal commissural neurons, motoneurons, dorsal root ganglion neurons, retinal ganglion cells, and callosal projection neurons during axon growth. Our (cultured dorsal spinal neurons of chick embryos) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…To investigate the localization of ASICs at growth cones, we performed immunocytochemistry for endogenous ASIC1a and ASIC2a, which are the primary ASIC subunits expressed in the central nervous systems in DIV3-DIV6 hippocampal neurons, using anti-ASIC1a and anti-ASIC2a antibodies. To facilitate the identification of growth cones, the neurons were coimmunostained with phalloidin (Huang et al, 2017). Immunocytochemistry was performed at DIV3 and DIV6 due to easy morphological recognition.…”
Section: Asics Localization At the Growth Cones Of Immature Cultured mentioning
confidence: 99%
“…To investigate the localization of ASICs at growth cones, we performed immunocytochemistry for endogenous ASIC1a and ASIC2a, which are the primary ASIC subunits expressed in the central nervous systems in DIV3-DIV6 hippocampal neurons, using anti-ASIC1a and anti-ASIC2a antibodies. To facilitate the identification of growth cones, the neurons were coimmunostained with phalloidin (Huang et al, 2017). Immunocytochemistry was performed at DIV3 and DIV6 due to easy morphological recognition.…”
Section: Asics Localization At the Growth Cones Of Immature Cultured mentioning
confidence: 99%
“…These results suggest that the inhibition of the K ATP channel may exacerbate neural degeneration, but the activation prevents degeneration. It has been reported that membrane excitability in the axonal growth cones of iScience Article embryonic neurons influences axonal growth (Huang et al, 2017). According to the report, increased membrane excitability inhibited axonal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal excitability is partly mediated by voltage‐gated ion channels that could transform the initial neuronal signaling to an action potential and give a rise to subsequent activities affected by biophysical properties and localization of these channels within neurons (Lewis et al., 2011). In excitable cells, Kv channels are key factors regulating membrane excitability by governing K + current changes (Huang et al., 2017). Kv channels are tetramers composed of four α subunits arranged around a central pore which controls the K + current efflux.…”
Section: Genetic Dysfunction Of Potassium Channels and Asd: From Genotypes To Phenotypesmentioning
confidence: 99%